Blast Performance of Multi-Layer Composite Door Panel with Energy Absorption Connectors - Shahab Ahmad; Shayan Zeb; Yonghui Wang; Muhammad Umair (Buildings)
Doors are considered vulnerable to failure in structures when subjected to extreme loads, such as blasts. Consequently, blast-resistant doors are designed to withstand blast pressure in important structures. This study developed a multi-layer Steel, Aluminum Foam, and Steel–Concrete–Steel composite door panel with Energy Absorption Connectors (SAFSCS-EACs) under near and far field blast loading using finite element analysis in LS-DYNA. Three dynamic response modes were observed based on the crushing strength of energy absorption connectors (EACs) for the SAFSCS-EAC composite door under both near and far field blasts. In addition, the membrane stretching phenomena was observed in the face steel plate. The AF shows a local densification in near field blasts and a global densification in far field blasts. For the SCS panel, a punching-like failure and a global flexural failure were observed in near and far field blasts, respectively. AF has a high energy absorption capacity as a first energy absorption layer, while the EAC also effectively dissipates blast energy through the rotation of the plastic hinges of curved steel plates, thereby reducing the damage to the SCS panel and increasing the door’s structural integrity. Moreover, to check the influence of the curved steel plate thickness of EACs and the core concrete thickness, a parametric study was carried out. The results showed that the blast resistance performance of the SAFSCS-EAC composite door could increase by appropriately designing the EAC curved steel plates’ thickness and ensuring that the compression displacement of the EAC under blast is close to its densification displacement. Additionally, increasing concrete thickness can reduce the degree of damage to the steel–concrete–steel composite panel during the blast, but it leads to a reduction in the energy dissipation of the EAC.